Epistemological-Methodological Criticism of Muhammad Syahrur In Islamic Studies (Case Study of Milk Al-Yamin Concept) - Muhammad Kholid Kholid (Tasfiyah: Jurnal Pemikiran Islam, 2021)
Muhammad Shahrur as one of the liberal scholar from Syria returned to fame with the emergence of Abdul Aziz's controversial dissertation which raised the theme of milk al-Yamīn. Shahrur is considered to have legalized adultery for interpreting milk al-Yamīn as an aqad iḥṣān or sexual partner outside of marriage. Coupled with derivatives of the concept of milk al-Yamīn Shahrur such as nikah mut'ah, musākanah (samen leven), 'urfī, grant, and muḥallil which have been agreed haram by jumhūr ulama. The methodology used in the writing of this article is descriptive-analytical critical to the Islamic worldview approach. This article seeks to describe the concept of milk al-Yamīn in the view of the Shahrur accompanied by criticism from various aspects, considering the authority of the Shahrur and assessing the methodology and epistemology of the Shahrur in interpreting the Qur'an. It was concluded that the shahrur's interpretation of the milk al-yamīn verses came out of the mainstream interpretation of the majority of scholars. Another problem lies in the inconsistency in the use of methodology, and the relativism of Syahrur epistemology.